Becoming pure: identifying generational classes of admixed individuals within lesser and greater scaup populations. Issue 3 (19th January 2016) - Lavretsky, Philip; Peters, Jeffrey L.; Winker, Kevin; Bahn, Volker; Kulikova, Irina; Zhuravlev, Yuri N.; Wilson, Robert E.; Barger, Chris; Gurney, Kirsty; McCracken, Kevin G.
Abstract: Estimating the frequency of hybridization is important to understand its evolutionary consequences and its effects on conservation efforts. In this study, we examined the extent of hybridization in two sister species of ducks that hybridize. We used mitochondrial control region sequences and 3589 double‐digest restriction‐associated DNA sequences (ddRADseq) to identifyadmixture between wild lesser scaup ( Aythya affinis ) and greater scaup ( A. marila ). Among 111 individuals, we found one introgressed mitochondrial DNA haplotype in lesser scaup and four in greater scaup. Likewise, based on the site‐frequency spectrum from autosomal DNA, gene flow was asymmetrical, with higher rates from lesser into greater scaup. However, using ddRADseq nuclear DNA, all individuals were assigned to their respective species with >0.95 posterior assignment probability. To examine the power for detectingadmixture, we simulated a breeding experiment in which empirical data were used to create F1 hybrids and nine generations (F2–F10) of backcrossing. F1 hybrids and F2, F3 and most F4 backcrosses were clearly distinguishable from pure individuals, but evidence of admixed histories was effectively lost after the fourth generation. Thus, we conclude that low interspecific assignment probabilities (0.011–0.043) for two lesser and nineteen greater scaup were consistent with admixed histories beyond the F3 generation. These results indicate that the propensity of these species to hybridize in the wild is low and largely asymmetric. When applied to species‐specific cases, our approach offers powerful utility for examining concerns of hybridization in conservation efforts, especially for determining the generational time until admixed histories are effectively lost through backcrossing.